Does endorsement of gender stereotypes predict women's interest in, and expressed likelihood to pursue an academic career in science or engineering? - Dunne, Christine, author; Canetto, Silvia Sara, advisor; Winterrowd, Erin, committee member; Gibbons, Alyssa, committee member; Herrera Alonso, Margarita, committee member (Colorado State University. Libraries, 2023)
Background: In recent decades much attention has been given in the United States (U.S.) to women's underrepresentation in science and engineering (SE) fields. Early theories were that women are simply not good at math and/or science, and that women are uninterested in SE. Both theories are not supported by evidence. To start with, in the U.S. women's representation in SE varies greatly by field (e.g., high representation in biology and low in computer science). Women's representation in SE also varies by country. For example, in Lithuania women represent the majority of engineers. This variability indicates that women are capable and interested in science, with social-cultural context (e.g., culture and opportunities) playing a major role in women's participation in SE. This study focused on the social-cultural context of women's participation in SE in the U.S. - specifically gender stereotypes and gender-ideology factors that are emerging as relevant to U.S. women's participation in SE fields mostly via studies of SE undergraduate students. The gender-ideology factors that are the focus of this study are: women's gender stereotypes of SE fields, gender stereotypes of SE individuals, SE women's goal orientation (e.g., self-versus other-growth focus), and SE women's family/work beliefs and expectations. This study examined whether these gender stereotypes and ideologies predict interest and expressed likelihood to pursue an academic career among graduate student women in SE. Regarding gender stereotypes of SE fields, U.S. studies of computer science (CS) and engineering undergraduate students suggest that when female students view these fields as more "masculine" they express less interest in SE careers (see Cheryan et al., 2017 for a review). Regarding gender stereotypes of SE individuals, U.S. studies of CS undergraduate students indicate that CS female students' interest and intention to pursue an academic career is lower when they view the field as masculine (e.g., Cheryan et al., 2011). Regarding goal orientation, U.S. studies conducted with undergraduate women in a variety of SE fields as well as psychology suggest that a focus on self-growth as an education goal is associated with greater interest in pursuing an SE career while a focus on others-growth is associated with less interest in pursuing an SE career (e.g., Diekman et al., 2010). Finally, with regard to family/work beliefs and expectations, quantitative survey studies of female SE undergraduates (e.g., in CS, Haines & Wallace, 2003; Sax, 2001) as well as qualitative and quantitative studies of female graduate students in science (e.g., in atmospheric sciences, Canetto et al., 2017; in chemistry and biology, Ferreira, 2003) suggest that women's interest and intention to pursue a leadership career in these fields are less strong when these women view themselves as having to take primary responsibility for family caregiving. A limitation of past U.S. studies of the social-cultural context of women in SE is that they mostly focused on undergraduate women or on professional women (e.g., Cech & Blair-Loy, 2019). An understudied SE educational stage is that of graduate school. Graduate school is when women make professional and personal decisions that support or interfere with their pursuit of a SE academic career. By the very fact of being in SE graduate school, SE graduate-student women have behaviorally challenged at least some SE stereotypes. The fact that they are investing in advanced SE education suggests SE-leadership ambition, including potentially, interest in a SE academic career. Aim: The purpose of this study was to examine the association, among SE female graduate students, between their interest in, and their expressed likelihood to pursue a career in academia, with their views in four domains: 1. Their views of academia, science in general, and their SE field, as relatively feminine or masculine; 2. Their views of women or men who excel in academia, science, and specific SE field, as relatively feminine or masculine; 3. Their educational and career goals, as mostly self-growth or others-growth oriented; and 4. Their views of women's and men's family responsibilities. Method: The sample consisted of 140 SE graduate student women at a large state university in the U.S. Participants were asked to respond to an online questionnaire that included questions regarding their endorsement of various gender stereotypes and ideologies, and questions about their interest in, and expressed likelihood of pursuing a career in academia. Results: Endorsement of gender stereotypes and of gender ideologies of work and family did not predict women's interest in, and stated likelihood to pursue an academic career. Endorsement of gender stereotypes and ideologies was low in this sample of female SE graduate students. The least endorsed were the family/work gender ideologies that competitiveness and nurturance vary by sex, and that mother should work for pay only if necessary. The relatively least rejected family/work gender ideology was the idea that a father's major responsibility is to provide financially for his children The most endorsed gender stereotypes were the belief that men excel more than women in SE, and that academia, science, and their specific field are masculine. Women also endorsed others-growth goals more than self-growth goals. Endorsement of self-growth or others-growth oriented career goals varied by field. Also, interest and expressed likelihood to pursue an academic career were both relatively low. Women's interest in an academic career varied by field and years in the program. Women in Math, Microbiology, and Atmospheric Sciences expressed the most interest in an academic career while women in Chemistry, Engineering and Statistics reported the least interest. The more years the women had spent in their graduate program the less interest in an academic career they expressed. Discussion: This study assessed the possible role of gender stereotypes of SE, gendered ideologies of career goals, and gendered ideologies of family and work, in women's interest and intention to pursue a SE academic career. A main finding is that SE female graduate students did not endorse these gender stereotypes and ideologies. The only stereotypes that they gave some credence to were the idea that men excel in SE more than women and the idea that academia, science, and their SE field are masculine. Interest and expressed likelihood to pursue an academic career were both relatively low. Not surprisingly then gender stereotypes of SE, gendered ideologies of career goals, and gendered ideologies of family and work did not predict interest and intention to pursue a SE academic career. In this study endorsement of gender stereotypes and ideologies varied by field. Specifically, women in Math, Microbiology, and Atmospheric Sciences expressed the most interest in an academic career while women in Chemistry, Engineering and Statistics reported the least interest. The uneven sizes of participants by field did not allow examination of patterns by field. A conclusion based on these findings is that the gender stereotypes of SE and of gendered ideologies of career goals and of family and work evaluated in this study do not matter to women's interest and expressed likelihood to pursue a SE academic career once women are in graduate school, though they have been found to be relevant to undergraduate women considering a SE higher education and leadership path (Cheryan et al., 2017), Other gender stereotypes and ideologies may be relevant to graduate school women's interest and intention to pursue a SE academic career. It is also conceivable that the self-report measures of gender stereotypes and of gendered ideologies used in this study were not sensitive-enough to capture the chosen constructs among women in SE graduate school. Interviews may be a more effective method to explore gender stereotypes and gender ideologies among women in SE graduate school. Given the variability in gender stereotypes and ideologies endorsement by field suggested by this study, future research should examine by SE discipline the relationship between endorsement of gender stereotypes and ideologies and SE career interest and expressed likelihood to pursue it. To evaluate what predicts women in SE graduate school's actual move into a SE academia career, future research should assess not only SE academic-career interest and stated likelihood to pursue an academic career but actual SE career behaviors, including SE academic career choice and progress in a SE academic career, via a longitudinal design.
Keywords: career; science; women; gender; academia; stereotypes